Droga do pełnej normalizacji stosunków między państwem i Kościołem oraz między PRL a Stolicą Apostolską - Alojzy Orszulik (Ksiegarnia Akademicka Publishing, 2014)
The article discusses the major steps on the long road to the establishment of full diplomatic relations between Polish People’s Republic and the Holy See, as well as efforts to ease the strained internal relations between the government and the Church. The political changes in the 70s led to renewal of the activity of the Common Commission consisting of the Church’s and government’s representatives. The article outlines the most important achievements of that commission and presents the drafts of legislation. It also presents the events that had finally led to the renewal of diplomatic relations in 1989.